Clinical improvement of a toddler with COVID-19 focal cerebral arteriopathy possibly due to intra-arterial nimodipine. (September 2022) - Avital, Dekel; Peretz, Shlomi; Perlow, Eliauh; Konen, Osnat; Inbar, Edna; Bulkowstein, Yarden; Nahum, Elhanan; Aharoni, Sharon; Vig, Lital Cohen; Nevo, Yoram; Auriel, Eitan; Straussberg, Rachel
Abstract: Pediatric stroke is considered an infrequent complication of COVID-19. Focal cerebral arteriopathy (FCA) is one of the most common causes of arterial ischemic stroke in a previously healthy child. The present report describes a toddler with FCA most likely induced by SARS-CoV-2 infection who showed significant clinical improvement that may be related to injection of intra-arterial nimodipine. To our knowledge, this is the first reported use of nimodipine in this setting. Highlights: This report describes a toddler with FCA most likely induced by SARS-CoV-2 infection. We describe significant clinical improvement possibly related to injection of intra-arterial nimodipine. To our knowledge, this is the first reported use of nimodipine in this setting. Efficacy and safety of intra-arterial nimodipine administration warrants further investigation.